'A world parliament of business'? The International Chamber of Commerce and its presidents in the twentieth century. Issue 2 (17th February 2023) - David, Thomas; Eichenberger, Pierre
Abstract: This article investigates the contribution of the International Chamber of Commerce (ICC), founded in Paris in 1920, to transnational business networks and communities. It is based on a prosopographic study of the 43 presidents of the ICC until 2000 and research in the archives of the ICC. Our results show that these men represented firms that were amongst the most powerful of their time. Furthermore, we show that the ICC presidents displayed heterogenous profiles, but spent an average of 10 years in the ICC before their election and remained active for many years after their tenure as president was over, allowing them to form a powerful transnational community. We investigate qualitatively the way the ICC presidents interacted to cement this transnational community. They met regularly over select events – such as the ' diner des sages' – and bonded over a common project: defending free trade and international business.